Puppet 5 : from beginner to pro - Arundel, John; Safari eBooks ([Place of publication not identified] : Packt, 2018)
"Puppet 5--from beginner to pro gets you up-and-running with the very latest features of Puppet 5, including Docker containers, Hiera data, and Amazon AWS cloud orchestration. Go from beginner to confident Puppet user with a series of clear, practical examples to help you manage every aspect of your server setup. This course teaches you how to install packages and config files, create users, set up scheduled jobs, provision cloud instances, build containers, and so much more."--Resource description page.
Title from title screen (viewed April 18, 2018).
Release date from resource description page (Safari, viewed April 18, 2018).
Keywords: Puppet (Computer file); Client/server computing; Software configuration management; Application software -- Development; High performance computing; Electronic books